Iowa CBC reporting form, Westfield, January 5, 1986 - Farmer, Larryet al (1986)
Checklist dated January 5, 1986 compiled by Larry Farmer. A list of birds sighted by Farmer and three others around Westfield. A total of 27 species and 1,459 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed